2022
DOI: 10.1111/lapo.12179
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory detention for criminal convictions: The reproduction of racial inequality throughU.S.immigration law

Abstract: Since the late 1980s, immigrants convicted of certain criminal offenses have been subject to mandatory detention during their deportation proceedings. Due to court backlog and complicated cases, noncitizens mandatorily detained in this way can be held for years at a time, without any legal right to a bail hearing. While political rhetoric and policy aims of the past three decades have painted so-called "criminal aliens" as a highly dangerous group from whom the American public needs protecting, the criminal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…It is worth noting that the aggravated felony provision is not a term borrowed from criminal legal doctrine, despite its resemblance to terminology indicating a serious crime. In fact, prior to 1988, it did not officially exist (Tosh, 2022). The 1986 ADAA expanded deportations related to drug offenses involving any federally controlled substance, while the 1988 ADAA created the term "aggravated felony" to identify the few noncitizens convicted of murder and illicit trafficking in drugs or firearms for apprehension, incarceration, and removal (Macías-Rojas, 2016).…”
Section: Creating the "Aggravated Felon" Outcastmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that the aggravated felony provision is not a term borrowed from criminal legal doctrine, despite its resemblance to terminology indicating a serious crime. In fact, prior to 1988, it did not officially exist (Tosh, 2022). The 1986 ADAA expanded deportations related to drug offenses involving any federally controlled substance, while the 1988 ADAA created the term "aggravated felony" to identify the few noncitizens convicted of murder and illicit trafficking in drugs or firearms for apprehension, incarceration, and removal (Macías-Rojas, 2016).…”
Section: Creating the "Aggravated Felon" Outcastmentioning
confidence: 99%
“…A study analyzing immigration court data between 2008 and 2018 (N=1,829,049) observed that 96% of noncitizens who had legal assistance appeared for all of their court hearings (Eagly & Shafer, 2020). However, once someone is in immigration detention, access to legal aid is substantially inhibited (Markowitz, 2009;Marouf, 2017) and legal representation is not provided (Tosh, 2022). Very few legal resources are readily available to noncitizens facing deportation unless they have the financial capacity to hire a lawyer or are fortunate enough to procure pro bono services which are typically scarce and in high demand (IRC, 2021).…”
Section: Service Planningmentioning
confidence: 99%
See 1 more Smart Citation